State Theocracy Perspective: Comparative Study of Caliphate and Vatican Church Governmental System - Khairunnas, Khairunnas; Fadhlia, Maudy Noor (Universitas Riau Kepulauan, 2025)
This paper presents a rigorous comparative study of the Islamic Caliphate and the Vatican City State, which operates under the governance of the Roman Catholic Church. Both institutions are anchored in authoritative theological doctrine, yet their historical evolution, mechanisms of legitimation, and global reception have unfolded in sharply contrasting manners. The Caliphate, conceived as the apex of Islamic authority uniting political and spiritual oversight, underwent a sequence of crises, culminating in the formal abolition in 1924, resulting in an enduring contest over its contemporary significance. The Vatican, by contrast, has displayed remarkable durability, its papal leadership securing a distinctive role in secular diplomacy and international governance, sustained by a coherent apparatus that transcends the territorial confines. The core finding is that the Vatican’s enduring stability stems from its successful transformation of theological mandate into widely recognized diplomatic legitimacy and transnational soft power. This contrasts with the Caliphate’s decline, which was accelerated by its structural entanglement with territorial governance and military power, leading to perceptions of it as an anachronism. This study contributes a novel cross-civilizational analytical template, treating both entities as theocratic formations. It compares their historical processes, modes of theological authority, and patterns of political reception within their respective polities. The principal innovation resides in this comparative frame, which illuminates how religion is mobilized as institutional power and addresses the contrasting degrees of global endorsement each system receives.Employing a qualitative, descriptive-analytical framework grounded in a multiple case study methodology, this inquiry seeks to advance religious political theory by unraveling the nuanced interplay between religious institutions and the apparatus of the state.